EFEKTIVITAS METODE DRILL TERHADAP KEMAMPUAN HAFALAN PESERTA DIDIK PADA MATA PELAJARAN FIQIH KELAS VI SDN 01 SUNGAI LIAT BANGKA - Fahrur Rozi; Wildan Saputra; Kuswatun Hasana; Rafika Agustiana; Dela Vina Sia; Syarnubi (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan, 2023)
The crucial problem that must be overcome at SDN 01 Sungai Liat Bangka is the low memorization ability of grade VI students on Fiqh material. This study aims to examine this method's effectiveness in overcoming the low memorization ability of grade VI students on Fiqh material. The research method used is a quantitative experiment type with only one group pre and post-design. This study showed an increase in memorization ability by 29 points and a Wilcoxon test result value of 0.001. Based on this, a conclusion can be drawn that the method is very effective and can overcome the low memorization ability of Fiqh material for grade VI students at SDN 01 Sungai Liat Bangka.